DOES FRACTIONAL RESERVE BANKING SYSTEM EXIST IN INDONESIAN ISLAMIC BANKING? - Syamlan, Yaser Taufik; Istiana, Nur (Journal of Islamic Monetary Economics and Finance, 2018)
Fractional Reserve Banking is the banking and financial system that have been applied in most countries around the world. This research aims to look at the impact empirically and at the contributions given from the components of fractional reserve banking against inflation that occurs in Sharia Commercial Banks and Sharia Business Unit. The fractional reserve banking components covered in these studies are statutory reserve requirement, total deposit, total financing, Mismatch Ratio, and Total non-performing financing. This research is using VAR VECM and ECM as analysis tools and also collecting secondary data from OJK that spanned from June 2014 to September 2018. The results of this research have found that Indonesian Islamic bank is doing the fractional reserve banking system (FRBS). Furthermore, the largest contributor of FRBS in Sharia Commercial Bank (BUS) is the Statutory Reserve Requirment while in sharia Business Unit the results showed that Third Party Fund and Mismatch ratio gives the greatest contributions against inflation. Interestingly, the UUS has greater contribution and shock to the inflation if we compare to the BUS. To prevent the effect of it in the future, controlling mismatch and introducing the irrevocable investment account might be the solutions.